THE URGENCY OF A NOTARY DEED IN CHANGING A INDIVIDUAL COMPANY INTO A CAPITAL PARTNERSHIP COMPANY - Yullananda; Usman, Rachmadi (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The Urgency of Notarial Deed in Changing a Sole Proprietorship to a Capital Partnership Company. This study aims to determine and analyze how a sole proprietorship changes to a capital partnership company and the urgency of a notarial deed in changing a sole proprietorship to a capital partnership company. This legal research uses a normative legal research type, the research approach used is the Statutory approach and the Conceptual Approach. A Sole Proprietorship is required to convert to a capital partnership company if the shareholder is more than one person and/or has exceeded the UMK qualification limit. as regulated in Article 9 of PP No. 8 of 2021 where the change in status is carried out through a notarial deed and registered electronically with the Minister of Law and Human Rights, if two Sole Proprietorships want to merge, it cannot be done through a formal merger as regulated in Law No. 40 of 2007. Because there are no regulations governing the process of changing additional shares through a merger between a Sole Proprietorship and another Sole Proprietorship. The change in legal form from a Sole Proprietorship to a Capital Partnership has significant legal and administrative consequences, thus requiring the formal involvement of a notary. The notarial deed is very important in this process because it is the legal basis needed to validate the existence and new structure of the company which is no longer owned by a single person based on Article 9 paragraph (2) of PP No. 8 of 2021.